Social Imaginaries of Childhood and Nursery School in Contemporary Society - Saiz-Linares, Ángela (2024)
Purpose. This scientific article presents a qualitative project aimed to critically analyse the collective imaginaries of childhood and nursery school held by three generations of children. Method. The research, framed within the qualitative-interpretative paradigm, used 45 semi-structured interviews with participants organised into three age groups (15-24, 25-54, and over 55) who were not professionally affiliated with the school. Findings. The study reveals the following key findings: a limiting vision of childhood, crossed by notions of innocence and vulnerability (particularly in older participants) and propaedeutic. An essentialist vision is less prevalent, especially among men. Likewise, in relation to school, the functions of assistance, protection and care (more present in men), and preparation, both academic (among younger participants) and social (among older participants), are dominant. Finally, the majority of participants identified age two as the optimal age to begin early childhood education. Conclusions. The study concludes by emphasizing the need for educational policies prioritizing equity and children’s rights, recognizing that policies of the facts are those that encourage transformations in social imaginaries.